Fiscal policy and economic growth: empirical evidence from EU countries - Benos, Nikos (Munich, 2009)
"This paper studies whether a reallocation of the components of public spending and revenues can enhance economic growth using data on 14 EU countries during 1990-2006. The results provide support for endogenous growth models. Specifically, the findings are: a) public expenditures on infrastructure (economic affairs, general public services) and property rights protection (defense, public order-safety) exert a positive impact on growth; b) distortionary taxation depresses growth; c) government expenditures on human capital enhancing activities (education, health, housing-community amenities, environment protection, recreation-culture-religion) and social protection do not have a significant growth effect. However, when coefficient heterogeneity across countries along with non-linearities are taken into account and public expenditures are further disaggregated, we have in addition that government outlays on education, defense and social protection are growth-enhancing. These findings are robust to changes in specification and estimation methodology."